ADEQUACY AND RELEVANCE OF SOCIAL STUDIES CONTENT AND CURRICULUM RESOURCE MATERIALS IN FULFILLING THE OBJECTIVES OF CITIZENSHIP EDUCATION: THE CASE OF THREE UPPER PRIMARY SCHOOLS IN BOTSWANA. - Ezron, Mangwaya; Emily, Mangwaya (IJRDO- Journal of Educational Research, 2016)
Citizenship education is a relatively new phenomenon in developing countries in general and Southern Africa in particular. Most southern African states teach citizenship education through one or more subjects. In Botswana citizenship education is taught through Social Studies. Where carrier subjects are used as a vehicle for teaching another subject challenges of balancing that subject’s content and the new subject are quite common. This study examines the adequacy and relevance of Social Studies content and resource materials in fulfilling the objectives of citizenship education. This qualitative study used a case study design. Utilizing focus group interviews and observations the study established that while content is generally adequate it does not take into account current Botswana contextual realities. The study recommends interventions which could be made use of to ensure that the changed Botswana social milleu is taken into account with respect to Social Studies content and resource materials.